Structure and kinematics of the reactivated Bicorb- Quesa diapir (Eastern Prebetics, Valencia) - Rubinat, M.; Roca, E. (TRABAJOS DE GEOLOGÍA, 2010)
The combined analysis of the Bicorb-Quesa diapir internal structure and the surroundingMesozoic cover allows to recognize the main characteristics of the Eastern Prebetics as well as to makea new and unique evolutionary model of a squeezed and later reactivated diapir. Specifically, this workpoints out: 1) the Bicorb-Quesa diapir was generated during the Early Miocene due to the movementof a basement normal fault ENE-WSW oriented and dipping towards the NNW, 2) the diapir wassqueezed during the Serravalian due to the displacement towards the NNW of the Jurassic-Cretaceouscover located in the footwall of the basement fault, and 3) the diapir was reactivated cutting the faultsand thrusts previously generated.